Implementasi Algoritma H.264 Untuk Kompresi File Pada Aplikasi Transfer File - Sianturi, Lamsihar Grasella (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Transfer files that have a relatively large size, result in a long transfer process and also consume a large internet quota in the sending process. Where the smaller the file size to be sent, the transfer process is also fast, and does not consume a lot of internet quota. To solve this problem, it is necessary to have compression which functions to reduce the size of the files to be transferred. One of the compression algorithms is H.264. The compression process using the H.264 algorithm is carried out when the file is sent, then when the file is received by the recipient, the file will be decompressed. Using the H.264 algorithm, the file will be sent successfully reducing the file size with a ratio of compression (RC) 2.5%, compression ratio (CR) 40%, redundancy (RD) 60%, and helping the transmission process of sending large files will be faster and save internet quota.